2015
DOI: 10.1136/gutjnl-2014-308536
|View full text |Cite
|
Sign up to set email alerts
|

Detection of precancerous gastric lesions and gastric cancer through exhaled breath

Abstract: Clinical Trials.gov number, NCT01420588 (3/11/2013).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
188
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 167 publications
(200 citation statements)
references
References 35 publications
3
188
0
1
Order By: Relevance
“…the chemical profiles of highly-and semi-VOCs in exhaled breath linked with disease. [3][4][5][6][7][8][9][10][11][12][13][14][15] The rationale behind this approach relies on the fact that VOCs generated by cellular metabolic pathways during a specific disease circulate in the blood stream and diffuse into exhaled breath, which is easily sampled. 4,16,17 In certain instances, analysis of breathprints offers several potential advantages, such as: (a) breath samples are non-invasive and easy to obtain; (b) breath contains less complicated mixtures than either serum or urine; and (c) breath testing has the potential for direct and real-time diagnosis and monitoring.…”
mentioning
confidence: 99%
“…the chemical profiles of highly-and semi-VOCs in exhaled breath linked with disease. [3][4][5][6][7][8][9][10][11][12][13][14][15] The rationale behind this approach relies on the fact that VOCs generated by cellular metabolic pathways during a specific disease circulate in the blood stream and diffuse into exhaled breath, which is easily sampled. 4,16,17 In certain instances, analysis of breathprints offers several potential advantages, such as: (a) breath samples are non-invasive and easy to obtain; (b) breath contains less complicated mixtures than either serum or urine; and (c) breath testing has the potential for direct and real-time diagnosis and monitoring.…”
mentioning
confidence: 99%
“…The future of prevention of gastric cancer deaths relies on the timely and early diagnosis and surveillance of patients with precancerous lesions as well as early detection of the cancer, making higher survival rates and lower healthcare costs per patient achievable [9,10]. Endoscopy with sampling of gastric biopsies is effective in screening of upper GI malignancies.…”
Section: Methodsmentioning
confidence: 99%
“…It has been a concern that breath analysis might be confounded by H. pylori infection or smoking behaviors. However, recent study showed that breath analysis with a breathsensing nanoarray was not affected by ages, sex, smoking, drinking habits, H. pylori infection or proton pump inhibitor medications [84].…”
Section: Volatile Organic Compounds As Markers Of Gastric Cancermentioning
confidence: 96%
“…Several studies have highlighted the potential of breath analysis for gastric cancer detection. The identified volatile organic compounds from gastric cancer patients included hexanoic acid, phenol, methyl phenol, ethyl phenol, 2-propenenitrile, 2-butoxy-ethanol, furfural, 6-methyl-5-hepten-2-one, hexadecane, 4-methyloctane, 1,2,3-trimethylbenzene, α-methyl-styrene, acetone, tetradecane, 3-methylpentane, hexane, 2,3-dimethylpentane, 2-methylhexane, and dodecane [83][84][85][86]. In addition, 2-butanone and menthol have been found at lower levels in gastric cancer patients comparing to controls.…”
Section: Volatile Organic Compounds As Markers Of Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation